Exploring Parental Involvement in Providing Education to Children with Disabilities in Nepal - Kunwar, Indra Bahadur (Dibyajyoti Journal, 2024)
This study aims to explore parental involvement in community schools for providing education to children with disabilities. It is based on qualitative with phenomenological research design. Three schools conducted with resource classes were chosen purposively from the Nawalparasi district. Interviews and questionnaires were used as research instruments to collect the data. The semi-structured interview schedule was applied for resource teachers and parents; whereas, questionnaire forms were used for teachers. The results demonstrate that parents’ attitudes toward these children are gradually moving positively; and they accept, respect and value their differences. Further, the results show that schools have not adequately involved parents in activities such as planning, monitoring and decision-making processes. Parents are less familiar with inclusive education policy and legal instruments. Although they are supportive of providing education for their children, their efforts are hindered by knowledge gap, poverty and inaccessibility of schools from their residence. Finally, Epstein’s framework of parental involvement partially fits with the parental involvement in community schools in Nepal. This study is equally important for policymakers and programmes designers at the federal, provincial and local level to ensure parents involvement in school education.